Data for forest sector planning in Peninsular Malaysia - Abd. Rahim, Abd. Rahman; Hadi, Yusuf; Abd. Ghani, Awang Noor (1987)
This paper reviews the status of foresty data collection in Peninsular Malaysia and suggests future data requirements for forest sector planning in the country. The data collected at the various levels in the Forest Department are described. Future data requirements are outlined after the planning problem, planning constraints and planning model have been identified.